Diaphragm electromyography guidance for a lung transplant recipient with difficult weaning from mechanical ventilation: A case report. Issue 23 (June 2018) - Xu, Yuanda; Qing, Qi; Liang, Minyong; Liang, Weibo; Lin, Zhimin; Wu, Weiliang; He, Weiqun; Liu, Xiaoqing; Luo, Yuanming; Li, Yimin; He, Jianxing
Abstract: Rationale: Many factors contribute to a complicated postoperative course following difficult weaning off a ventilator after lung transplantation. Patient concerns: A female patient underwent a successful surgery but received a size-mismatched lung graft. The graft had been pruned before transplantation. She experienced delayed ventilator weaning 3 days after lung transplantation. Diagnoses: A postoperative X-ray revealed a normal mediastinal structure and diaphragm position. Diaphragmatic function was assessed by diaphragm electromyography (EMGdi) via esophageal and surface electrodes. EMGdi showed decreased left compound motor action potentials (CMAPs), prolonged left phrenic nerve conduction time (PNCT), failure to induce right CMAPs and PNCT under bilateral magnetic stimulation, and right phrenic nerve injury. Interventions: She was treated with neural nutritional support and prescribed rehabilitation measures such as strengthening limb activities on the bed. Outcomes: The patient finally achieved satisfactory outcomes after an early diagnosis and medical interventions. Lessons: Lung size mismatch before transplantation and phrenic nerve injury during surgery should be avoided wherever possible.